2023
DOI: 10.1111/mec.16919
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the avian gut microbiota: The influence of host state and environmental heterogeneity

Abstract: The gut microbiota have important consequences for host biological processes and there is some evidence that they also affect fitness. However, the complex, interactive nature of ecological factors that influence the gut microbiota has scarcely been investigated in natural populations. We sampled the gut microbiota of wild great tits (Parus major) at different life stages allowing us to evaluate how microbiota varied with respect to a diverse range of key ecological factors of two broad types: (1) host state, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 164 publications
1
4
0
Order By: Relevance
“…A plethora of studies have reported robust links between the nesting environment and chick gut microbiota [26,28,36,98]. Our findings align with the "nidobiome" concept, which integrates the collective effects of parents, nest conditions, and nestling interactions during microbiome assembly and their contribution over the developmental stages [24].…”
Section: Age Difference and Nest Similarity Driving Gut Compositional...supporting
confidence: 80%
“…A plethora of studies have reported robust links between the nesting environment and chick gut microbiota [26,28,36,98]. Our findings align with the "nidobiome" concept, which integrates the collective effects of parents, nest conditions, and nestling interactions during microbiome assembly and their contribution over the developmental stages [24].…”
Section: Age Difference and Nest Similarity Driving Gut Compositional...supporting
confidence: 80%
“…A plethora of studies have reported robust links between the nesting environment and chick gut microbiota [ 26 , 28 , 36 , 98 ]. Our findings align with the ”nidobiome” concept, which integrates the collective effects of parents, nest conditions, and nestling interactions during microbiome assembly and their contribution over the developmental stages [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such heterogeneity is not unusual for a wild system (e.g. Baniel et al., 2021; Risely et al., 2022; Somers et al., 2023), particularly in passerines whose short intestinal tracts (an adaptation to flight) may make them more susceptible to transient environmental microbes (Bodawatta et al., 2021; Song et al., 2020). However, high levels of heterogeneity may eliminate, or make it difficult to detect, consistent longitudinal changes in GM diversity and stability.…”
Section: Discussionmentioning
confidence: 99%